Reproductive women’s health in the XXI century - Овсянникова, Т. В. (REPRODUCTIVE ENDOCRINOLOGY, 2013)
This article is an overview of a number of reports of national and foreign experts presented at the international conference «Eff ective and safe continuation of the pregnancy at the early and late stages», initiated by companies Bionorica SE and Besins Healthcare. In particular, addressed the issue of miscarriage pregnancy, preterm labor, treatment of luteal phase defi ciency, use of herbal medicines during pregnancy, including infl ammatory diseases of the urinary excretory tract.